Editorial - Mackinlay, Elizabeth; Nakata, Martin (The Australian Journal of Indigenous Education, 2016)
We are honoured to present this issue of The Australian Journal of Indigenous Education. It is a sentiment we express each time an issue is released but rarely do we unpack what this is exactly. Formerly, the Aboriginal Child at School, The Australian Journal of Indigenous Education has resisted and persisted the tide of state, Federal and global politics which ebb and flow through our work in Aboriginal and Torres Strait Islander education, and Indigenous education more broadly. Appearing sometimes as friend, sometimes as foe, and perhaps many more times as both, such practices, policies and politics present ongoing challenges for us but nevertheless, we are still here searching for and speaking particular kinds of justice into the space for the Indigenous children, their families and communities that matter to us. The current educational climate of neoliberalism — replete as it is with individualism, competition, measurement and accountability — is certainly no different but we are still here — persisting and resisting. We are still on our way to the kind of education we seek for Indigenous peoples at all levels locally, nationally and globally and the papers in this issue represent that search. To quote bell hooks in Teaching to Transgress, a much loved scholar in critical pedagogy, ‘the academy is not paradise. But learning is a place where paradise can be created. The classroom, with all its limitation, remains a location of possibility’ (1994, p. 207). The ongoing search to move beyond boundaries characterises much of the work that appears in The Australian Journal of Indigenous Education and it is this sentiment which we are honoured to present.